Fiber Communication System Based on FBG As Dispersion Compensator, Design And Experimental Setup - A. Kadhim, Shehab; A. Kazr, Karrar; H. Ali, Alaa; I. Mahmood, Aseel (International Journal of Engineering and Technology, 2019)
The technological progress in the means of transmission of information is very fast and it becomes necessary to obtain high speed in data transmission and high data rate. The developments in optical communication systems cover these needs, so the developments in these systems become an urgent need. However, despite all characteristics and advantages of optical communication systems, there is the dis-persion problem. In this research we will get rid of this problem in practice through the use of fiber Bragg grating connected to two separate and different wavelengths then connecting them to the Wavelength Division Multiplexing and send them to a distance of 3 Km then calculate the amount of dispersion in the signal with and without fiber Bragg grating and compare the results.Â